2011
DOI: 10.1143/jpsj.80.044711
|View full text |Cite
|
Sign up to set email alerts
|

Possible Odd-Frequency Superconductivity in Strong-Coupling Electron–Phonon Systems

Abstract: A possibility of the odd-frequency pairing in the strong-coupling electron-phonon systems is discussed. Using the Holstein-Hubbard model, we demonstrate that the anomalously soft Einstein mode with the frequency ω E ≪ ω c (ω c is the order of the renormalized bandwidth) mediates the s-wave odd-frequency triplet pairing against the ordinary even-frequency singlet pairing. It is necessary for the emergence of the odd-frequency pairing that the pairing interaction is strongly retarded as well as the strong coupli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 62 publications
3
53
1
Order By: Relevance
“…[17][18][19][20][21][22] Diamagnetic odd-frequency pairs could form a homogeneous superconducting ground state. 19,21,22 Although several theoretical papers have suggested possibilities of odd-frequency superconductivity in strongly correlated electron systems [23][24][25] , no clear experimental evidence of odd-frequency superconductivity has been presented so far. It is difficult to resolve directly the frequency symmetry of pair potentials.…”
Section: -10mentioning
confidence: 99%
“…[17][18][19][20][21][22] Diamagnetic odd-frequency pairs could form a homogeneous superconducting ground state. 19,21,22 Although several theoretical papers have suggested possibilities of odd-frequency superconductivity in strongly correlated electron systems [23][24][25] , no clear experimental evidence of odd-frequency superconductivity has been presented so far. It is difficult to resolve directly the frequency symmetry of pair potentials.…”
Section: -10mentioning
confidence: 99%
“…However, using mean-field-type theory, it has been shown that the second-order phase transition into the OF superconductivity is unstable in general [27,28]. In this case, the Meissner kernel has the sign opposite to that in the ordinary BCS theory.…”
Section: Introductionmentioning
confidence: 99%
“…From another point of view, it is also discussed within the path-integral approach that the homogeneous OF superconducting state cannot be stable in a Hermitian mean-field Hamiltonian, but can exist if one assumes the non-Hermitian relations for anomalous Green functions [28,36,37]. Another study has demonstrated that the positive Meissner effect is found using the composite-operator description [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…After that, Balatsky and Abrahams suggested an odd-ω spin-singlet pairing state 14 in a study on high-T C cuprates while, of course, the consensus is now that a conventional even-frequency (even-ω) spin-singlet d-wave pairing state is realized in the high-T C cuprates. A lot of intensive studies on the odd-ω pairing state follow these proposals in both bulk [15][16][17][18][19][20][21][22] and inhomogeneous systems. [23][24][25][26][27] Since there have been predicted many anomalous novel quantum phenomena in odd-ω pairings generated in inhomogeneous systems, [28][29][30][31][32][33][34][35][36][37][38] it is a challenging issue to pursue the possible bulk odd-ω superconductor from various aspects now.…”
Section: Introductionmentioning
confidence: 82%